Hubungan Kadar Hba1c dan Kolesterol Total dengan Kejadian Peripheral Arterial Disease pada Pasien Diabetes Mellitus Tipe 2 - Puspitasari, Metana; Mahmuda, Iin Novita Nurhayati; Chandra, Ilham Edgar Fadhila; Najib, Yazid Aufa (Syntax Corporation, 2023)
Type 2 diabetes mellitus (DMT2) is caused by the inability of pancreatic beta cells to produce insulin and tissue resistance to insulin. T2DM requires ongoing treatment to control blood sugar and prevent complications such as Peripheral Arterial Disease (PAD) and high cholesterol problems. HbA1c measurement and total cholesterol monitoring are important in diabetes management and prevention of serious complications. An observational analytical study, cross-sectional approach was conducted in September 2022 at Gatak Health Center, Sukoharjo on 65 patients with T2DM. The data were analyzed with a 2x2 chi square test table. The results of the study found that 21 (32.3%) research subjects experienced PAD. Bivariate test between total cholesterol and Hba1c with consecutive PAD incidence p = 0.377; p = 0.416. It can be concluded that there is no significant relationship between the variables total cholesterol and Hba1c with the incidence of PAD. This can be caused by lack of control over other risk factors for PAD events such as smoking, hypertension, duration of diabetes, age, and gender.